Teologi Kritis di Masa Teror: STrategi Pendidikan Teologi Teroris - Agus Iswanto (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2006)
This article tries to discus about possibility of theology reconstruction (religious comprehension) in its relation with terrorism action in the name of religion in Islamic education practice. The first, the writer discuses about meanings of theology and terrorism, which are key concepts in this study. Then to investigate the roots, of terrorism in the name of God through religion fundamentalism concept with jihad whose mascot whose roots is political problem. According to the writer, this problem needs the new formula of theology in Islamic education practice. This theology is critical theology inspired by the Islamic universal good norms (The Qur'an and Sunnah). This theology always criticizes comprehension of religious which is loaded by political self interest of certain group caused conflict.